2021
DOI: 10.1097/jnn.0000000000000585
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Perspectives on Pain Assessment and Opioid Use: International Neuroscience Nursing Research Symposium Conference Proceedings

Abstract: INTRODUCTION: In August of 2020, the 4th International Neuroscience Nursing Research Symposium was held. The purpose of the symposium was to share neuroscience nursing research from around the world. One of the topics thought most notable that stimulated a crucial conversation was how different countries assessed pain and their use of opioids for pain management. BACKGROUND: Neuroscience nurses are global. What is not known is their experience with and what challenges exist with pain management for human being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…In addition, as conference proceedings were excluded, some relevant neuroscience nursing research was not included that reported on the cultural perspectives on pain assessment and opioid use. 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as conference proceedings were excluded, some relevant neuroscience nursing research was not included that reported on the cultural perspectives on pain assessment and opioid use. 6…”
Section: Discussionmentioning
confidence: 99%
“…Although an attempt was made to capture all relevant research, there are doubtless topics of importance to some neuroscience nurses that are not reflected here. In addition, as conference proceedings were excluded, some relevant neuroscience nursing research was not included that reported on the cultural perspectives on pain assessment and opioid use 6 …”
Section: Discussionmentioning
confidence: 99%
“…5,10,12 Although pharmacological methods including opioid consumption hold an important place in pain management, patient-related factors, including age, sex, education, emotional status, site and type of surgery, cultural values, and pain beliefs, also affect the intensity of postoperative pain. 1,11,[13][14][15] Pain beliefs have been noted to affect patients' ability to cope with pain. 11,16 Gradually increasing in importance, pain beliefs are considered as one of the cornerstones in conceptualizing pain in cognitive terms.…”
mentioning
confidence: 99%
“…21,23 Beliefs about the causes and expectations of pain and therapeutic outcomes shape the process of recovery by influencing the willingness to receive treatment, patient outcomes, coping with pain, functionality, and attitudes and behaviors. 11,13,20 Positive pain beliefs increase personal control over pain, whereas negative pain beliefs cause patients to feel helpless, leading to ineffective pain control. 22 For this reason, inclusion of pain beliefs in the evaluation of pain may aid effective pain management.…”
mentioning
confidence: 99%
“…14,15 Despite the development of evidence-based training courses, pain management strategies, and pain management teams, nurses continue to experience knowledge deficits and negative attitudes toward pain management. 16 A cross-sectional study found the total correct percentage score on the Knowledge and Attitude Survey Regarding Pain (KASRP) was 36.6 among Ethiopian nurses and stated that nurses had inadequate knowledge and negative attitudes regarding pain management. 17 Similarly, a multicenter cross-sectional study in Italy reported the correct percentage score on KASRP of 31.21 and emphasized that nurses need to improve knowledge and attitudes regarding pain management.…”
mentioning
confidence: 99%